Vulvar condylomatosis after sex reassignment surgery in a male-to-female transsexual: Complete response to imiquimod cream - Trinidad Labanca; Ivan Mañero (Elsevier, 2017)
Background: The number of patients seeking sex reassignment surgery is increasing. Approximately 1:30,000 adult males and 1: 100,000 adult females seek this procedure. Neovaginal-related disorders after sex reassignment surgery are increasingly more common. Vulvar condylomatosis is the clinical manifestation of HPV 6- and 11 infection in biological women. The same HPV-subtypes are associated with anogenital warts and penile intraepithelial neoplasia in biological men. We aim to present a case of vulvar condylomatosis after sex reassignment surgery in a male-to-female transsexual and its complete response to 5% imiquimod cream. Case: We describe a case of a 19-year-old female transexual who presented one year after male to female sex reassignment surgery by inverted penile skin vaginoplasty with condyloma accuminata of the vulva. The patient had a complete response to imiquimod 5% cream 12 weeks after initiation of treatment. Conclusion: Gynecologists should be prepared to treat neovaginal-related disorders in male-to-female transsexuals.